2022
DOI: 10.1039/d2fo00485b
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined impact of texture manipulation on oral processing behaviours among faster and slower eaters

Abstract: Background: Food texture can moderate eating rate and ad-libitum energy intake. Many foods are combined with condiments when consumed and the texture and eating properties differ considerably between condiments and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…44 A recent experiment by R. Janani and colleagues demonstrated how combinations of specific food texture modifications can be used to alter micro-structural patterns of oral processing and eating speed. 45 A closer understanding of these changes will create new opportunities to moderate eating behaviours and metabolic response in the future. Variations in salivary amylase activity were not associated with time spent above normal glucose range, which is in line with findings from previous research.…”
Section: Discussionmentioning
confidence: 99%
“…44 A recent experiment by R. Janani and colleagues demonstrated how combinations of specific food texture modifications can be used to alter micro-structural patterns of oral processing and eating speed. 45 A closer understanding of these changes will create new opportunities to moderate eating behaviours and metabolic response in the future. Variations in salivary amylase activity were not associated with time spent above normal glucose range, which is in line with findings from previous research.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Margarine addition speeded up ER of the bread slices mainly via a steep decrease in chews per g. Previous studies showed similar effects of condiment addition on of a carrier food on ER, which were also explained by a decreased number of chewing cycles. 11,24,34 Condiments moistens and softens the food in the oral cavity. 35 Adding a condiment, especially a fatbased one like margarine, requires less saliva to form a compact bolus that is safe to swallow and this will speed up the ER 21 and explains the steep decrease in chews per g when adding margarine in this study.…”
Section: Papermentioning
confidence: 99%
“…Most studies investigating ER and intake behaviour by manipulating one parameter, 3 whereas it might be beneficial to change more parameters to impact oral processing. 11 The aim of this study was to understand more complex textural changes on oral processing by systemically changing two textural parameters using bread as model food. For this purpose, two bread types with different structures and texture were selected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations